Computational study of the presence of defects in semiconducting polymers on exciton formation - Correia, Helena M. G. (2011)
The ability of deposition of semiconducting polymers in solution is one of the key advantages of using this type of materials in organic solar cells or light emitting diodes, among their optical and electronic properties. After deposition, polymeric films presents an amorphous structure due to the very weak coupling of adjacent polymeric chains, that strongly influences the optoelectronic properties of the devices where they are used. In addition, is possible to find out throughout the film several defects that result from the polymerization process and device manufacturing, among others. These defects can lead to the formation of deep energetic sites that influence excitons dynamics, reducing exciton diffusion, decreasing the fluorescence effect, and working like quenching sites allowing easy exciton dissociation into a pair of charges of opposite sign. Although it is known that the existence of these defects clearly decreases the optoelectronic efficiency, it is not known how they work at molecular level on exciton formation and their effect on exciton energy in polymer chromophores. In this communication we present our latest results in understanding the influence of well-known polymer defects on exciton formation, by performing a computational study using a self-consistent quantum molecular dynamics method. Our results show that the energetic disorder in polymeric systems, that influence exciton dynamics, depends on the type of defect that influences intramolecular exciton localization as well as exciton energy.